Biologic therapy for psoriasis - still searching for the best target - Teresa Pinto-Almeida; Tiago Torres (Sociedade Brasileira de Dermatologia, 2014)
Psoriasis is a chronic skin disease that results from the complex interaction between genetic and environmental factors. Over the last few decades, scientific evidence has redirected the focus of therapeutic studies to the immunologic pathways underlying its pathogenesis. This led to the biologic boom that we are currently experiencing, with the development and approval of targeted progressively more selective biological therapies and ongoing clinical trials of increasingly specific drugs, given their important implications for long-term efficacy and safety. Nevertheless, the search for the optimal biologic is still ongoing, and the best target has yet to be found.